The Influence of Job Demand on the Performance of Generation Z Employees at PT XYZ Indonesia - Putri, Nur Rizkia; Fauzobihi; Ilham, Wanda (ITQAN: Journal of Islamic Economics, Management, and Finance, 2026)
In the competitive manufacturing industry, companies must manage human resources optimally to achieve performance targets. This study aims to analyze the effect of job demand on the performance of Generation Z employees. The study population was 210 employees, with a sample size of 140 people determined using the Slovin formula with a 5% error rate. The study employed a quantitative approach using a questionnaire. The collected data were analyzed with SPSS version 25, incorporating validity and reliability tests, descriptive analysis, and simple linear regression. The results showed that job demand had a significant effect on performance. The coefficient of determination (r²) value of 0.183 indicates that 18.3% of performance variation is influenced by job demand. In comparison, the remaining 81.7% is influenced by other factors such as job resources, leadership, and work motivation. Thus, the greater the work demands perceived by employees, the greater their drive to show optimal performance, as long as the workload remains within reasonable limits. This finding should be considered by companies when designing an optimal workload, which can encourage performance without sacrificing the psychological or physical well-being of Generation Z employees.